Dampak Fraud Pasca Pandemi Covid 19: Bukti di Asia Pasifik dan Indonesia - Natalis Christian; Helen Febriana (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2023)
The global Covid-19 pandemic event is feared to cause fraud to occur which has a negative impact financially and non-financially. This study was conducted to see the financial and non-financial impact of fraud between Indonesia and the Asia Pacific after the Covid-19 pandemic. This research was conducted using quantitative research and a case study method that uses secondary data as a reference. The secondary data used comes from articles from supervisory institutions and public accounting firms, the Association of Certified Fraud Examiners (ACFE), Indonesia Corruption Watch (ICW), the Corruption Eradication Commission (KPK), and Price waterhouse Coopers (PwC), and other sources. The object of this research is fraud cases that occurred in Indonesia and the Asia Pacific. Based on various studies, fraud cases in both Indonesia and the Asia Pacific, which were also triggered by the influence of the Covid-19 pandemic in 2020-2022, have decreased even though the potential for corruption in Indonesia has increased. Globally, fraud is predicted to increase which can have a greater adverse impact both financially (loss of money) and non-financially (damage to reputation, legal action, and so on). Studies conducted to assess the impact of fraud from various sources can be applied as material to broaden insights and references for future research.